2000
DOI: 10.1046/j.1365-3059.2000.00491.x
|View full text |Cite
|
Sign up to set email alerts
|

Cell wall‐degrading enzymes produced in vitro by isolates of Phaeosphaeria nodorum differing in aggressiveness

Abstract: The relationships between in vitro production of cell wall-degrading enzymes and aggressiveness of three Phaeosphaeria nodorum isolates were investigated. When grown in liquid medium containing 1% cell wall from wheat leaves as the carbon source, the isolates secreted xylanase, a-arabinosidase, b-xylosidase, polygalacturonase, b-galactosidase, cellulase, b-1,3-glucanase, b-glucosidase, acetyl esterase and butyrate esterase. Time-course experiments showed different levels of enzyme production and different kine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
40
0
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(47 citation statements)
references
References 28 publications
6
40
0
1
Order By: Relevance
“…It is generally acknowledged that many plant-pathogenic fungi can produce a variety of CWDEs that are involved in plant pathogenesis (Lalaoui et al, 2000;Lehtinen, 1993). These enzymes are particularly important for so-called 'rot' pathogens when attacking their hosts by breaking down host tissue (Lehtinen, 1993).…”
Section: Impact Of Fsr1 On Selected Cwdes In F Verticillioidesmentioning
confidence: 99%
“…It is generally acknowledged that many plant-pathogenic fungi can produce a variety of CWDEs that are involved in plant pathogenesis (Lalaoui et al, 2000;Lehtinen, 1993). These enzymes are particularly important for so-called 'rot' pathogens when attacking their hosts by breaking down host tissue (Lehtinen, 1993).…”
Section: Impact Of Fsr1 On Selected Cwdes In F Verticillioidesmentioning
confidence: 99%
“…For hydrolysis of PCW as well as FCW to be efficient and complete, synergistic action of several enzymes is required (Alfonso et al 1995a;Collins et al 2005;Lalaoui et al 2000;Perez-Leblic et al 1982;Reyes et al 1977).…”
Section: Resultsmentioning
confidence: 99%
“…Fungal glycosidases such as b-galactosidases, xylosidases, and arabinosidases release sugar moieties that can be used by a Communicated by Erko Stackebrandt. fungus as a nutritional source during its growth through plant tissues (Akimitsu et al 2004). It has been demonstrated that cereal pathogens produce more xylanase activity than other cell wall-degrading enzymes that use cereal cell walls as a C source (Apel et al 1993;Degefu et al 2001;Giesbert et al 1998;Lalaoui et al 2000;Phalip et al 2009;Wanjiru et al 2002;Wu et al 1995Wu et al , 2006. In graminaceous crops and grasses, arabino-xylan accounts for up to 40% of the walls (Beliën et al 2006;Carpita 1996;Hatsch et al 2006;Labavitch and Ray 1978).…”
Section: Introductionmentioning
confidence: 99%
“…Another human pathogen, Candida parapsilosis, has emerged as an important cause of human candidiasis, often responsible for pathological lesions of the nails (Gautret et al 2000;Krcmery and Barnes 2002;Kiffer-Moreira et al 2007). In addition, the heterothallic ascomycete, Phaeosphaeria nodorum, is a common necrotrophic plant pathogen causing leaf blotch and glume blotch diseases on wheat (Triticum aestivum) (Lalaoui et al 2000;Stukenbrock et al 2006). Neither A. fumigatus nor C. parapsilosis or P. nodorum have been reported to have industrial biotechnology application potential.…”
Section: Resultsmentioning
confidence: 99%